Chaperones and prions - Chernoff, Yury (Henry Stewart Talks, 2008)
Prion diseases, Prions as self-propagating amyloids, Yeast prions as protein-based heritable elements, Prion detection, Crucial role of the chaperone protein Hsp104 in the propagation of yeast prions, Chaperone-mediated fragmentation turns amyloids into infectious or heritable prions, Effects of the Hsp70 and Hsp40 proteins on yeast prions, Other modulators of prion formation and propagation: cytoskeleton and ubiquitin system
Updated at 2020/09/26